Obesity negatively impacts lung function in children and adolescents. Issue 10 (25th October 2013) - Davidson, Warren J.; Mackenzie‐Rife, Kelly A.; Witmans, Manisha B.; Montgomery, Mark D.; Ball, Geoff D.C.; Egbogah, Shirley; Eves, Neil D.
Summary Objectives To investigate the relationship between weight status (body mass index [BMI] percentile and BMI z‐score) and lung volumes in healthy children and adolescents. Hypotheses We hypothesized that: (a) there would be a significant inverse relationship between age‐ and sex‐specific BMI distribution and functional residual capacity (FRC), and expiratory reserve volume (ERV), respectively; and (b) obese children would have significantly reduced FRC and ERV compared to their non‐obese peers. Methods The medical records of all individuals who successfully performed pulmonary function testing between 2000 and 2007 at two university children's hospitals were reviewed. Participants were excluded if they had cardiopulmonary, neuromuscular, or chest wall disease. Results Of 1, 469 record reviewed, 327 subjects met study criteria. Percent predicted ERV was lowest in the obese group (P < 0.001) while residual volume (RV) was lowest in the overweight and obese groups (P < 0.001). Underweight participants had a lower percent predicted forced vital capacity (FVC) (P = 0.027) and vital capacity (VC; P = 0.039). Obese participants had the lowest FEV1/FVC (P < 0.001). A positive linear relationship existed between BMI z‐score and percent predicted FVC, VC, and diffusing capacity of carbon monoxide (DLCO). A negative linear relationship was found between BMI z‐score and percent predicted FRC, ERV, RV, and absolute FEV1/FVC. Conclusions Our results show that increasing weight status in children and adolescents is associated with a general reduction in lung volume measurements, which may reflect impaired lung function, increased respiratory symptoms, and decreased functional status. Pediatr Pulmonol. 2014; 49:1003–1010. © 2013 Wiley Periodicals, Inc.